Quantitation of bioactive compounds in cultivated fruit crops - Lok, Veronica Li wen (2013)
Malaysia is a melting pot of unique and exotic tropical fruits such as Artocarpus heterophyllus Lam. (Jackfruit) and Nephelium lappaceum L. (Rambutan). The present study deals with the determination of total phenolic and flavonoid content in A. heterophyllus Lam. (Jackfruit) and N. lappaceum L. (Rambutan) which is responsible for antioxidant activity exhibited by the fruits. The amount of total phenols and flavonoids were analyzed with the Folin-Ciocalteu assay and colorimetric method, respectively. Gallic acid was used as a standard compound for the total phenol estimation and was expressed as mg of GAE / 100 g of sample. While quercetin was used as a standard compound for the total flavonoids and were expressed as mg of QCE / 100 g of sample. The total phenolics ranged from 68.768 ± 0.35 mg GAE / 100 g sample to 100.822 ± 0.12 mg GAE / 100 g sample in the extracts. The maximum phenolic content was found in the aqueous extract of A. heterophyllus (100.822 ± 0.12 mg GAE / 100 g sample). The total flavonoid varies from 14.33 ± 1.44 QCE / 100 g sample to 38.50 ± 2.5 QCE / 100 g sample in the extracts. The maximum flavonoid content was found in the aqueous extract of A. heterophyllus (38.50 ± 2.5 QCE / 100 g sample). Thus the presence of phenolics and flavonoids in substantial amount is supporting evidence in order to recommend A. heterophyllus and N lappaceum for the pharmaceutical and cosmetic industry. It should also be made as public information to advice people about the benefits of these fruits in their dietary intake.